2017
DOI: 10.1111/1745-9133.12307
|View full text |Cite
|
Sign up to set email alerts
|

Building the Ties that Bind, Breaking the Ties that Don't

Abstract: Research Summary Although family support is an important protective factor against recidivism, less is known about how the domain of family works with other elements of the risk–need–responsivity model. By using the Serious and Violent Offenders Reentry Initiative (SVORI) data, we explore whether family and criminal peers have (a) independent and (b) interdependent effects on substance abuse and crime after release from prison. The outcomes of multilevel models demonstrate that the risk factor of criminal peer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
27
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 59 publications
(42 citation statements)
references
References 41 publications
4
27
0
1
Order By: Relevance
“…Although age appears to relate only to polysubstance use and the lagged measure of the dependent measure is only significant in the criminal offending model, both within-individual changes in family conflict and delinquent peers post-release are related to elevated levels of offending and polysubstance use. This finding meshes with prior work on the importance of peers and family in the reentry process (e.g., Mowen and Visher 2015; Boman and Mowen 2017). Moving toward exploring these factors further, we now turn to results of cross-lagged dynamic panel models examining family conflict and delinquent peers as outcomes.…”
Section: Resultssupporting
confidence: 85%
See 2 more Smart Citations
“…Although age appears to relate only to polysubstance use and the lagged measure of the dependent measure is only significant in the criminal offending model, both within-individual changes in family conflict and delinquent peers post-release are related to elevated levels of offending and polysubstance use. This finding meshes with prior work on the importance of peers and family in the reentry process (e.g., Mowen and Visher 2015; Boman and Mowen 2017). Moving toward exploring these factors further, we now turn to results of cross-lagged dynamic panel models examining family conflict and delinquent peers as outcomes.…”
Section: Resultssupporting
confidence: 85%
“…First, given the deleterious outcomes associated with family conflict (e.g., Conger and Elder 1994) and delinquent peer associations (McGloin et al 2014) on adolescent development more broadly, we seek to examine whether family conflict and peer delinquency incite crime and substance use among youth undergoing the reentry process. Following prior literature on adolescent development outcomes associated with family conflict and peer delinquency, we expect that (Hypothesis 1) increases in family conflict (e.g., Mowen and Visher 2015) and (Hypothesis 2) increases in delinquent peers (e.g., Boman and Mowen 2017) will relate to greater levels of substance use and criminal offending during the challenging time of reentry. Second, toward building a developmentally-grounded perspective on how specific experiences during incarceration and reentry relate to the development of family conflict and delinquent peer associations, we then examine factors that relate to each during reintegration.…”
Section: Current Studymentioning
confidence: 95%
See 1 more Smart Citation
“…Because the vast majority of individuals who spend time in prison will be released (Carson and Anderson 2016; Travis 2005), understanding factors that promote successful reintegration has become an important task for the development of both theory and policy (see Seiter and Kadela 2003). Although research has highlighted a number of dimensions as important for successful reintegration including employment (Seiter and Kadela 2003; Uggen 2000), mental health care (Mallik-Kane and Visher 2008), treatment and reentry preparation (Prendergast 2009; Robbins, Martin, and Surratt 2007), and desistance from criminal peers (Boman and Mowen 2017), perhaps more so than any other factor, family support has been highlighted as an extraordinarily vital component for reentry success (see, generally, Arditti and Few 2006; Braman 2004; Breese, Ra’el, and Grant 2000; Naser and La Vigne 2006; Naser and Visher 2006; Nelson, Deess, and Allen 1999; Shapiro and Schwartz 2001; Visher and Courtney 2007; Western et al 2015).…”
mentioning
confidence: 99%
“…The importance of family support has been highlighted in both qualitative and quantitative research efforts using a variety of samples across the United States. Existing research has shown that family support relates to decreased recidivism (Boman and Mowen 2017; Shollenberger 2009; Visher and Courtney 2007), increased odds of employment (Berg and Huebner 2011; Visher, Debus, and Yahner 2008), and better mental health outcomes (Grieb et al 2014; Wallace et al 2016) during reentry. As Naser and Visher (2006:20) find, “for most former prisoners, relationships with family members are critical to successful reintegration.” In addition to a moderate level of empirical support, these findings can be understood via criminological theory.…”
mentioning
confidence: 99%